Trends and projections of the global burden of T2DM-associated CKD related to high BMI: A global burden of disease study 2021 - Jing Zhang; Wenxuan Li; Zhen Sun; Yunyang Wang; Yu Xue; Ke Si; Yajing Huang; Wenshan Lv; Lili Xu; Yangang Wang (PLoS ONE, 2025)
Background Type 2 diabetic-associated chronic kidney disease (T2DM-Associated CKD), a leading cause of end-stage renal disease, is exacerbated by rising particularly high body mass index (BMI) rates. This study examines the global burden of T2DM-Associated CKD attributable to high BMI from 1990 to 2021 and projects future trends using the Global Burden of Disease (GBD) 2021 data. Methods GBD 2021 data from 204 countries were analyzed to assess mortality, disability-adjusted life years (DALYs) and corresponding age-standardized rates of T2DM-Associated CKD linked to high BMI. Bayesian Age-Period-Cohort modeling was used for projections, with stratification by age, gender, and Socio-Demographic Index (SDI). Statistical analyses were conducted using R software. Results In 2021, high BMI-related T2DM-Associated CKD caused 173,263 deaths and 4.3 million DALYs. Age-standardized rates declined globally but showed regional disparities, with Andean Latin America having the highest burden. Women had higher absolute burdens, while men showed higher standardized rates. Projections indicate continued increases in mortality and DALY rates through 2050. Emerging therapies, such as GLP-1 receptor agonists (RAs) and SGLT2 inhibitors (SGLT2i), could potentially alter these trends, especially in high-risk regions. Conclusions High BMI significantly drives the T2DM-Associated CKD burden, necessitating targeted overweight/obesity prevention and improved healthcare access, particularly in high-risk regions. Monitoring trends is crucial for effective interventions.